Computer Simulation of the Vertical Zone Melting Method for Manufacturing Ingots of Bismuth-Telluride-Based Thermoelectric Materials with a Square Cross-Section - Lysko, V.V.; Kuz, R.V.; Razinkov, V.V.; Havryliuk, S.S. (Journal of Thermoelectricity, 2025)
It has been shown that the losses of thermoelectric material when cutting disks with a circular cross-section into branches for thermoelements are significant – the weight of defective legs can reach 20–30%, depending on the sizes of the legs and disks. This can be avoided by manufacturing thermoelectric material in the form of ingots with a square cross-section. The results of computer simulation of vertical zone melting for producing square cross-section ingots of bismuth-telluride-based thermoelectric materials are presented. The dependence of the shape of the crystallization front on the geometric dimensions of the heater and coolers, their temperatures, movement speed, and other technological parameters is given. These dependencies have been analyzed for different materials used in the manufacture of the container in which the material is grown – quartz, ceramics, and graphite. A multifactor computer optimization of process parameters and equipment design has been conducted. Bibl. 26, Figs. 9.